A Silver Lining : Productive and Inclusive Aging for Malaysia - World Bank (World Bank, Kuala Lumpur, 2020)
In 2020, Malaysia passes a crucial milestone in its demographic trajectory and becomes an aging society. Driven by a precipitous decline in fertility accompanied by a sustained rise in life expectancy, in recent years Malaysia has seen an uptick in the pace of demographic change. Rapid aging will be one of the most crucial megatrends affecting Malaysia in coming decades, raising policy challenges in areas such as employment, income security, health care, and aged care. The term silver economy has been coined to encompass all sources of opportunities that arise from economic activities that serve the needs and demands of older persons. While rapid aging is crucially important and will become even more so in coming decades, through the right choice of policies, the government of Malaysia can help the country achieve productive and inclusive aging. The Coronavirus (COVID-19) pandemic has resulted in an unprecedented crisis with an enormous health and human toll, as well as exacerbated many of the policy challenges raised by aging both in the short term and more structurally. The report analyzes Malaysia’s demographic, socioeconomic and macroeconomic contexts, as well as three select key policy areas where critical knowledge gaps exist–employment, income security, and aged care.